Use of Digital Games Media in Mathematical Thinking Courses to Improve Literacy Skills - Emas Marlina (UPT Publikasi Universitas Islam Bandung, 2023)
This study aims to improve the literacy skills taken by students in the mathematical thinking course through the use of digital media. The method used in this research is classroom research by observing the improvement of learning carried out in the mathematical thinking course class through the steps of the Hopkins model with a cycle of planning, action, observation, and reflection. The subjects of this study were students of the Mathematics Education Study Program at one university in Bandung totaling 34 people. The statistics used in this study are descriptive statistics with the data analyzed qualitative data. The data collected includes observations, questionnaires, reflections, and the Digital Games application on Microsoft Powerpoint. Based on the analysis of observations, it can be concluded that the use of digital games media in mathematical thinking courses can improve literacy skills. Based on the questionnaire analysis, students responded positively to the use of Digital Games media in mathematical thinking courses.